Biocatalytic performance of Butyribacterium methylotrophicum in the long-term conversion of synthesis gas produced from low-grade lignin gasification by Butyribacterium methylotrophicum [Resumo] - Pacheco, Marta (2022)
ABSTRACT: Second-generation biorefineries produce large streams of low-grade lignin. Its thermochemical conversion, through gasification, enables the carbon recovery from an otherwise recalcitrant by-product. The main product of gasification is producer synthesis gas (PS), which is mainly composed by carbon monoxide (CO), carbon dioxide (CO2), hydrogen (H2), methane (CH4) and minor impurities. Carboxydotrophic acetogenic bacteria can utilize CO and CO2 as carbon and energy source, and convert them into biomass, biofuels and biochemicals through the Wood-Ljungdahl pathway.